Propuesta de un manual de funciones, valuación de puestos por puntos y un reglamento de admisión y empleo para la empresa Enetsa de la ciudad de Quito - Ordóñez Calero, Arteman Evitelio (2015)
The present thesis is realized for the purpose of choosing for the title of Commercial Engineer, which ride as topic “Proposal of a manual of functions, positions valuation for points and a regulation of admission and employment for the company Enetsa of the city of Quito”, being this the general target of the thesis. Inside the specific targets that decided for the thesis we can detail the following ones: To realize the analysis of the existing charges in the company Enetsa of the city of Quito, to Carry out the description of each of the charges, to Propose an organizational structure, to Prepare the Manual of Functions of easy use between its managers, Valuar the positions of each of the personnel and to Design a Regulation of Admission and Employment. The achievement of the thesis did it to itself based on the following scheme. In its first part there consists the review of the literature which is shaped by the referential frame in which there is done a historical critique of the company “Enetsa“; its economic activity, mission, vision, politics and values; and the conceptual frame in this one does to itself a conceptualization regarding manuals of functions, valuation of positions and admission and employment with its respective skills and procedures, this is of big importance in the investigation because across the conceptual frame the thesis leans back. Later in the second part of the thesis we describe the materials and methods used inside which we are provided with the descriptive method that it allowed to make one describe of the current situation of the company; scientific method served to write the theoretical part of the thesis; inductive method served to evaluate the information of the company and based on this to realize them proposed established in the thesis and the deductive method that allowed to show concepts, procedures and skills that served for the making of the manual of functions, valuation of positions and regulation of admission and employment. Later the results, in this point there was realized the tabulation of the information obtained across skills as the interview to mister President, Manager and surveys realized to 37 employees of the Ecuadoran Domestic enterprise of Transports S.A.“ Enetsa” of the city of Quito, this allowed us to determine that the company at present is provided with 16 fixed charges; 37,84 % of the personnel works in the company more than 5 years; 5,40 % possesses qualifications of third level; 75,68 % of the personnel does not know such important elements of the company as the mission, vision, politics and values; 83,78 % indicated that the company is not provided with definite flow charts; 94,59 it indicates that the company must tell with guides how there are functions manuals to face the daily works; 83,78 % of the interrogated persons shows that the company is not provided with functions sheets for the development of the daily activities; 51,35 % of the interrogated persons thinks that the functions are not well distributed; for the revenue of the personnel to the company to 37,83 % only they realized a preliminary interview, to 16,22 % they realized selection interviews and you prove 29,73 % of work, what demonstrates to us that a due process is not realized for the admission and employment in the company; 78,38 % has not received any training on the part of the company; the company this alone year has qualified 10,81 % of its labor staff; 97,30 % of the interrogated persons thinks that it is important to receive trainings to improve the performance in the functions; inside the contracts of employment that the company signed with the personnel has 75,68 % it corresponds for contracts in indefinite time; 70,27 % thinks that the company determines its wages empirically, 67,57 % does not agree with the remuneration that receives in accordance with the charge that it occupies and 97,30 % thinks that the company should be provided with technical systems of valuation of positions in order to achieve its correct remuneration. Next with the information obtained in the results, one proceeded to the discussion in which, one developed the proposals for the company “Enetsa“, the same ones that were realized in accordance with the current needs of the same one, in this one they consist the new organizational structure shaped by 5 hierarchic levels; new values aligned to the mission and vision of the company; manual of functions in which there is specified the charge, the requests and the respective functions; positions valuations across the method of valuation of positions for points taking like factors to the knowledge and skill, effort, responsibility and working conditions; and finally the regulation of admission and employment, in which there does emphasis to itself the application of specializing technical functions as they are: recruiting, selection, hiring, induction and economic compensation. As conclusions we can indicate that the Ecuadoran Domestic enterprise of Transports S.A. “Enetsa“, possesses an informal organizational structure since this one has not been defined explicitly; it is provided with 16 fixed charges; there does not exist a suitable diffusion of the mission, vision and values; the functions for every charge are not well distributed, it does not exist functions sheets; it does not carry technical processes out for the admission of its personnel; and it is not provided with technical systems for positions valuation. As recommendations so that the Ecuadoran Domestic enterprise of Transports S.A. “Enetsa“, realizes a correct Personnel management it is recommended to the managers to take to consideration the proposals realized in this investigation. And finally there is the bibliography, the annexes and the index